1993
DOI: 10.1111/j.1936-4490.1993.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors Contributing to Satisfaction with End‐User Computing Process

Abstract: This study attempts to identify the factors contributing to overall satisfaction in end‐user computing (EUC) process. The sample of end‐users, who worked in a micro or minicomputer environment, corresponds to the first three of the six categories in Rockart and Flannery's (1983) typology: nonprogramming end‐users, command level users, and end‐user programmers. A survey was conducted asking respondents to rate their satisfaction with EUC on various attributes of not only the EUC application but also the EUC pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…H4 was also supported indicating that user support is positively and significantly related to IS success dimensions. The findings are consistent with studies by Mirani and King (1994), Vijayaraman and Ramakrishna (1990), Bergeron et al (1990), Buyukkurt and Vass (1993) and Igbaria et al (1997). The positive outcome may be due to the implementation of the e-government systems that needs to be maintained, monitored and supported from time to time.…”
Section: Relationship Between Technological Factors and Is Successsupporting
confidence: 88%
See 1 more Smart Citation
“…H4 was also supported indicating that user support is positively and significantly related to IS success dimensions. The findings are consistent with studies by Mirani and King (1994), Vijayaraman and Ramakrishna (1990), Bergeron et al (1990), Buyukkurt and Vass (1993) and Igbaria et al (1997). The positive outcome may be due to the implementation of the e-government systems that needs to be maintained, monitored and supported from time to time.…”
Section: Relationship Between Technological Factors and Is Successsupporting
confidence: 88%
“…User support deals with the technical support and help given to users in terms of operating the information systems in the organization. The importance of user support to the success of user computing has been highlighted in many studies (Amoroso, 1988;Amoroso and Cheney, 1991;Buyukkurt and Vass, 1993;Igbaria et al, 1997). Many researchers have found significant support for the relationship between personal computing success and user support (Mirani and King, 1994;Vijayaraman and Ramakrishna, 1990;Bergeron et al, 1990).…”
Section: User Supportmentioning
confidence: 99%
“…In the context of digital library systems, the provision of librarian assistance for library users would be one of the facilitating conditions that influence the usage of the systems. A number of studies highlighted the importance of technical support for the successful diffusion of computer system usage in organizations (e.g., Buyukkurt & Vass, 1993;Igbaria, 1994;Robey, 1979). The availability of technical support then can lead to a higher rate of computer system acceptance.…”
Section: Library Assistancementioning
confidence: 97%
“…Studies have shown that the adoption of technology is dependent largely on the support environment around that technology, and the help available from others (Buyukkurt and Vass, 1993;Igbaria, 1994;Westcott, 1985). The availability of such help is a precondition to the perception of a technology's ease of use.…”
Section: Librarian Assistancementioning
confidence: 99%